Acceptance, Usability and Usefulness of WebLab-Deusto from the Students Point of View - Garcia-Zubia, Javier; Hernandez, Unai; Angulo, Ignacio; Orduña, Pablo; Irurzun, Jaime (International Journal of Online and Biomedical Engineering (iJOE), 2009)
In the engineering curriculum, remote labs are becoming a popular learning tool. The advantages of these laboratories and the different deployments have been analyzed many times, but in this paper we want to show the results of the studentsâ?? opinion about WebLab-Deusto as a learning tool. This work is focused on the subjects Programmable Logic (PL) in the third year of Electronics Engineering and in Electronics Design (ED) of the fifth year of the same degree. The paper presents the results of the surveys done by students since 2004. This survey consists of fifteen questions and its main objective is to measure the acceptance, usability and usefulness of the remote laboratory developed at University of Deusto from the students point of view.